Risk factors for symptomatic vascular events in giant cell arteritis: a study of 254 patients with large-vessel imaging at diagnosis. (June 2021) - de Mornac, Donatienne; Agard, Christian; Hardouin, Jean-Benoit; Hamidou, Mohamed; Connault, Jérôme; Masseau, Agathe; Espitia-Thibault, Alexandra; Artifoni, Mathieu; Ngohou, Chan; Perrin, François; Graveleau, Julie; Durant, Cécile; et al.
Aims: To identify factors associated with vascular events in patients with giant cell arteritis (GCA). Methods: We performed a retrospective study of GCA patients diagnosed over a 20-year-period, who all underwent vascular imaging evaluation at diagnosis. Symptomatic vascular events were defined as the occurrence of any aortic event (aortic dissection or symptomatic aortic aneurysm), stroke, myocardial infarction, limb or mesenteric ischemia and de novo lower limbs arteritis stage 3 or 4. Patients with symptomatic vascular event (VE+) and without were compared, and risk factors were identified in a multivariable analysis. Results: Thirty-nine (15.4%) of the 254 included patients experienced at least one symptomatic vascular event during follow-up, with a median time of 21.5 months. Arterial hypertension, diabetes, lower limbs arteritis or vascular complication at diagnosis were more frequent in VE+ patients ( p  < 0.05), as an abnormal computed tomography (CT)-scan at diagnosis ( p  = 0.04), aortitis ( p  = 0.01), particularly of the descending thoracic aorta ( p  = 0.03) and atheroma ( p  = 0.03). Deaths were more frequent in the VE+ group (37.1 versus 10.3%, p  = 0.0003). In multivariable analysis, aortic surgery [hazard ratio (HR): 10.46 (1.41–77.80), p  = 0.02], stroke [HR: 22.32 (3.69–135.05), p  < 0.001], upper limb ischemia [HR: 20.27 (2.05–200.12), p  = 0.01], lower limb ischemia [HR: 76.57 (2.89–2027.69), p  = 0.009], aortic atheroma [HR: 3.06 (1.06–8.82), p  = 0.04] and aortitis of the descending thoracic aorta on CT-scan at diagnosis [HR: 4.64 (1.56–13.75), p  = 0.006] were independent predictive factors of a vascular event. Conclusion: In this study on GCA cases with large vessels imaging at diagnosis, aortic surgery, stroke, upper or lower limb ischemia, aortic atheroma and aortitis of the descending thoracic aorta on CT-scan, at GCA diagnosis, were independent predictive factors of a vascular event. Plain language summary: Risk factors for symptomatic vascular events in giant cell arteritis This study was performed to identify the risk factors for developing symptomatic vascular event during giant cell arteritis (GCA) because these are poorly known. We performed a retrospective study of GCA patients diagnosed over a 20-year-period, who all underwent vascular imaging evaluation at diagnosis. Patients with symptomatic vascular event (VE+) and without (VE-) were compared, and risk factors were identified in a multivariable analysis. Thirty-nine patients experienced at least one symptomatic vascular event during follow-up, with a median time of 21.5 months. Arterial hypertension, diabetes, lower limbs arteritis or vascular complication at diagnosis were significantly more frequent in VE+ patients, as an abnormal CT-scan at diagnosis, aortitis, particularly of the descending thoracic aorta and atheroma. Deaths were more frequent in the VE+ group. Among 254 GCA patients, 39 experienced at least one vascular event during follow-up. Aortic surgery, stroke, upper and lower limb ischemia were vascular event risk factors. Aortic atheroma and descending thoracic aorta aortitis on CT-scan were vascular event risk factors. This study on GCA cases with large vessels imaging at diagnosis, showed that aortic surgery, stroke, upper or lower limb ischemia, aortic atheroma and aortitis of the descending thoracic aorta on CT-scan, at GCA diagnosis, were independent predictive factors of a vascular event.